Dentists’ role in obstructive sleep apnea: A more comprehensive review - Najla S. Alrejaye; Hamdan Al-Jahdali (Sleep Epidemiology)
Obstructive Sleep Apnea (OSA) is a prevalent disorder with significant morbidity and mortality. Positive Airway Pressure (PAP) therapy is considered the gold standard and the most effective management option for OSA. However, a considerable number of patients are unable to tolerate or decline PAP therapy and seek alternative or complementary treatments. Studies have reported insufficient knowledge among physicians regarding OSA management, including the role of dentists. Furthermore, the focus on dentists' role in OSA management has primarily been limited to the provision of oral appliances, despite the potential for dentists to play a more significant role. This review article aims to provide a comprehensive and clear understanding of the dentists' role in OSA management to assist physicians in better recognizing their patients' needs and providing timely referrals for more efficient management.